Polish Independent Press Summary, no. 75 (1990) - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
A digest of Polish underground press (including articles, tables of content, and book covers) compiled by members of the RFE Polish Underground Publications Unit to be used in a daily 20-minute broadcast on Polish samizdat. Extract from Ex Libris, test issue (1990). Extract from Wybór, no. 1 (10 June 1990). Table of Contents from Europa, no. 5 (1989). Table of Contents from Krytyka, no. 32/33 (1990). Table of Contents from Obóz, no. 18 (1990). Table of Contents from Na Głos, no. 1 (1990). Table of Contents from Czas Kultury, no. 16 (May 1990). Table of Contents from Czas Kultury, no. 17 (June 1990). Table of Contents from Arka, no. 29 (1990). Extract from Von Krockow, Christian. Czas Kobiet: Wspomnienia z Pomorza 1944-1947 według relacji Libussy Fritz-Krockow. Warszawa: CDN, 1990. Cover Page from Konderak, Adam. Bibliografia Prasy Solidarności: 28.VIII.1980-12.XII.1981. Lublin: Oficyna Wydawnicza Fundacji Solidarności Regionu Środkowowschodniego, 1990. Cover Page from Markowa, Anna. Rozwałka. Katowice: Oficyna Śląska, 1989. Cover Page from Modzelewski, Karol. Między Umową a Wojną. Warszawa: Niezależna Oficyna Wydawnicza, 1989. Cover Page from Świadectwo: Wspomnienia Dymitra Szostakowicza tak jak zostały opowiedziane Solomonowi Wołkowowi i w opracowaniu tegoż. Warszawa: Niezależna Oficyna Wydawnicza, 1989. Cover Page from Bocheński, Józef. ...Tylko nie mogą wrócić ...: Dowody w sprawie sowieckiego mordu w Katyniu. [S.l.]: Text, Atu, 1990. Cover Page from Pipes, Richard. Rosja Carów. Warszawa: Krąg, 1990. Cover Page from Awtorchanow, Abdurchman. Od Andropowa do Gorbaczowa. Warszawa: Baza, 1990. Cover Page from Kurczewski, Jacek, ed. Stalinizm. Warszawa: UW IPSiR, 1989. Cover Page from Hassner, Pierre. Świat Epoki Jałty: Szkice polityczne. Warszawa: In Plus, 1990. Cover Page from Morin, Edgar. O Naturze Związku Radzieckiego. Warszawa: Volumen, 1990. Cover Page from Podhoretz, Norman. Krwawe Skrzyżowanie. Warszawa: Niezależna Oficyna Wydawnicza, 1989. Cover Page from Najder, Zdzisław. Wymiary Polskich Spraw: 1982-1990. Warszawa: Most, 1990. Cover Page from Fisher, A.G.A. Z Dziejów Partactw Ekonomicznych: Podręcznik dla Mężów Stanu.